Inclusion Complexes of Cassava Starch as Potential Carriers for Curcumin Drug Delivery - Khaira, Hasnatul
Curcumin is a hydrophobic compound found in the turmeric rhizome of (Curcuma Longa). Curcumin has extensive pharmacological activities such as anti-inflammatory, anti- mutagenic, anti-oxidant, anti-cancer, anti microbial, and anti-parasitic. However, the use of curcumin compounds in the pharmaceutical field is still limited, due to it’s low solubility in water and low stability at physiological pH, and is susceptible to light and heat conditions. The formation of the starch?curcumin inclusion complex via direct mixing is one of the solutions to increase the efficiency of delivery and stability of curcumin. The resulting inclusion complexes were analyzed using FTIR, XRD, SEM, and TGA. The FTIR results show there is a shift of wave number which is curcumin from 1631 cm-1 (the alkene group) to the wave number 1641 cm-1, 1501 cm-1 (the aromatic group) to the wave number 1521 cm-1, and at 978 cm-1 (an alkoxy group) on shifted to 998 cm-1. This indicates that there are cemical interaction between curcumin and starch. The XRD characterization of resulting complexes showed a new peak at 2? is 24.6º indicating the presence of V7?amylose. The results of TGA analysis showed that starch started to degrade at 261 ºC and the complex started to degrade at 231 ºC. This shows that the complex has lower thermal stability tha starch but higher than curcumin which is started to degrade at 183 ºC. Degradation test using ?-amylase enzyme showed that the presence of curcumin in starch decreased the activity of ?-amylase enzyme.